2002
DOI: 10.1017/s0967199402002265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hoechst 33342 staining on developmental competence of prepubertal goat oocytes

Abstract: This study was undertaken to evaluate the effects of Hoechst staining on nuclear maturation and fertilisation when used at different stages of in vitro maturation (IVM) in prepubertal goat oocytes. Oocytes were matured in TCM1999 supplemented with 10% fetal bovine serum, 10 μg LH/ml, 10 μg FSH/ml and 1 μM 17β-estradiol for 27 h. Frozen-thawed sperm cells were prepared by centrifugation in a discontinuous Percoll gradient and resuspended in DMH medium with 20% steer serum. Oocytes were fertilised in DMH medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…6), observation of PVS formation appears to be a useful way of distinguishing between SN-and NSN-type oocytes without Hoechst staining. To determine the chromatin configuration, the oocyte DNA must be stained with Hoechst and visualized under ultraviolet (UV) light, which is reported to decrease meiotic competence [6,35,36]. Previous studies using Hoechst staining to determine the chromatin configuration have shown that even low concentrations of Hoechst combined with short exposure to UV light decrease the competence of preimplantation development [7,12,37].…”
Section: Discussionmentioning
confidence: 99%
“…6), observation of PVS formation appears to be a useful way of distinguishing between SN-and NSN-type oocytes without Hoechst staining. To determine the chromatin configuration, the oocyte DNA must be stained with Hoechst and visualized under ultraviolet (UV) light, which is reported to decrease meiotic competence [6,35,36]. Previous studies using Hoechst staining to determine the chromatin configuration have shown that even low concentrations of Hoechst combined with short exposure to UV light decrease the competence of preimplantation development [7,12,37].…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, antes do processo de enucleação, o oócito é marcado com Hoechst 33342, o qual apresenta uma fluorescência azul quando exposto à luz ultravioleta (Velilla et al, 2002).…”
Section: Enucleação Dos Oócitosunclassified
“…Contudo tem sido demonstrado um efeito negativo da exposição do oócito à luz UV (Velilla et al, 2002), conseqüentemente tem sido recomendado não expor o citoplasma a esta radiação, mas sim apenas a porção removida presente na pipeta de aspiração (Chesné, 2006). Outra substância utilizada junto com o Hoechst 33342 é a citocalasina B cuja ação despolimeriza os microfilamentos e impede a citocinese (Sá et al, 2006).…”
Section: Enucleação Dos Oócitosunclassified
“…The sperm pellet was diluted and maintained in DMH supplemented with 20% (v/v) steer serum for at least 1 h at 38.5 • C. Sperm cells were then diluted in the fertilization medium, composed of DMH, 20% steer serum and 7.75 mM calcium lactate, to inseminate with a final sperm concentration of 2 × 10 6 sperm cells/ml. Sperm and oocyte co-incubation was performed in tubes at 38.5 • C for 20 h (the time at which two pronuclei could be easily observed by Hoechst staining in prepubertal goat oocytes; Velilla et al, 2002).…”
Section: In Vitro Fertilizationmentioning
confidence: 99%